Comparison of Physical Education Learning Motivation between The Science Department and The Social Sciences Department - Elbadiansyah; Masyni; Reza Fatchurahman; Irwan Hadi Saputra (Postgraduate, University of Mataram, 2024)
This study aims to determine whether there are differences in motivation to study physical education between science majors and social studies majors at SMA Negeri 1 Subang. The research method used is non-experimental (ex post facto) with a comparative design, namely the research is directed to compare one sample group with another group. In this study, researchers wanted to compare the level of motivation to learn science majors with social studies majors at SMA Negeri 1 Samarinda. The population in this study were students of class XII IPA and XII IPS SMA Negeri 1 Samarinda, totaling 364 students with a sample taken of 20% of the population, namely 69 respondents. The instrument used in this study was a motivational questionnaire which was tested for validity and reliability by the author with the results of 25 valid items out of 27 existing item items and a reliability level of 0.902. In this study, the hypothesis was tested using the independent sample t-test formula with a result of 0.002 < 0.05, so with these results there was a significant difference between the motivation to study physical education majoring in science and social studies at SMA Negeri 1 Samarinda (exceeding the classical completeness standard). The results of this research show that animated learning media can improve responsiveness and science learning outcomes in special sports classes.